Spironolactone therapy in infants with congestive heart failure secondary to congenital heart disease. Issue 12 (December 1981) - Hobbins, S M; Fowler, R S; Rowe, R D; Korey, A G
Abstract : The efficacy of treatment with spironolactone for congestive heart failure secondary to congenital heart disease was studied in 21 infants under 1 year of age. All received digoxin and chlorothiazide. In addition, group A (n = 10) was given supplements of potassium and group B (n = 11) received spironolactone. Daily clinical observations of vital signs, weight, hepatomegaly, and vomiting were recorded. Paired t test analysis showed significant reduction in liver size and weight (P less than 0.01) and respiratory rate (P less than 0.05) in group B, and less significant decreases in group A. The incidence of vomiting was slightly lower in group B. We conclude that the addition of spironolactone hastens and enhances the response to standard treatment with digoxin and chlorothiazide in infants with congestive heart failure.